Development and Evaluation of Biodegradable Chitosan Films of Metronidazole and Levofloxacin for the Management of Periodontitis - Khan G.; Yadav S.K.; Patel R.R.; Nath G.; Bansal M.; Mishra B. (My University, 2025)
Metronidazole (MZ) and levofloxacin (LF) are widely employed for treatment of periodontitis, but high oral dose and resistance development after long-term oral administration limit their use. The aim of this study was to alleviate shortcomings in the treatment of periodontitis by fabrication of intrapocket, biodegradable films of chitosan (CS) loaded with MZ and LF meant for inserting into periodontal pockets to treat infections. The films were developed by solvent casting technique using propylene glycol as plasticizer and glutaraldehyde as crosslinking agent. Their physical characteristics, such as drug content, surface pH, swelling index, and folding endurance, exhibited results within limit. Further, FTIR and DSC studies revealed stability of films and compatibility between drugs and excipients. SEM images of films showed the presence of free drug particles on the surface causing burst effect. In vitro release in McIlvaine buffer pH 6.6 was of sustained nature assisted by the burst effect. CS and crosslinking agent concentrations negatively affected drug release and positively affected T90 (time for releasing 90% of the drug) due to altered matrix density. In contrast, the plasticizer concentration increases membrane permeability and hence increased drug release, lowering T90. Crosslinked films demonstrated sustained release up to 7 days. The antibacterial efficacy of films was tested on Staphylococcus aureus and Escherichia coli, indicating good antibacterial activity. Clinical trials on patients proved the therapeutic efficacy of the films by a significant (p < 0.05) decrease in the clinical markers of periodontitis, i.e. gingival index, plaque index and pocket depth. Conclusively, the films of MZ and LF were successful tools for the management of periodontitis. © 2015, American Association of Pharmaceutical Scientists.